New research on labor relations and the performance of university HR/IR programs - Lewin, David, 1943-; Kaufman, Bruce E. (Emerald, 2001)
This volume presents five studies on key dimensions of union-management relations. Topics examined include union representation, financial consequences of unionism, wage determination, workplace innovation and conflict resolution in unionized enterprises in North America. In addition, the volume features four papers that examine university degree programmes in human resource management and industrial relations and, in particular, the extent to which the programmes provide students with the skills and competencies currently in demand by employers.
This volume presents five studies on key dimensions of union-management relations. Topics examined include union representation, financial consequences of unionism and wage determination, workplace innovation, and conflict resolution in unionized enterprises in North America.
Keywords: Personnel management.; elektronické knihy; electronic books